A Novel BLDC-Like DTC Control Technique for Induction Motors. (21st June 2012) - Rossi, Andrea; Concari, Carlo
Abstract : DC brushless motors are widely adopted for their simplicity of control, even in sensorless configuration, and their high torque density. On the other hand, induction motors are very economical due to the absence of permanent magnets; for the same reason they can easily be driven in the flux-weakening region to attain a wide speed range. Nevertheless, high dynamic induction motors drives, based on field-oriented (FOC) or predictive control, require large amounts of computing power and are rather sensitive to motor parameter variations. This paper presents a simple DTC induction motor control algorithm based on a well-known BLDC control technique, which allows to realize a high dynamic induction motor speed control with wide speed range. The firmware implementation is very compact and occupies a low amount of program memory, comparable to volt-per-Hertz- (V/f-) based control algorithms. The novel control algorithm presents also good performance and low current ripple and can be implemented on a low-cost motion control DSP without resorting to high-frequency PWM.